2020
DOI: 10.3390/acoustics2010005
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation and Phase Velocity of Elastic Wave in Textured Polycrystals with Ellipsoidal Grains of Arbitrary Crystal Symmetry

Abstract: This study extends the second-order attenuation (SOA) model for elastic waves in texture-free inhomogeneous cubic polycrystalline materials with equiaxed grains to textured polycrystals with ellipsoidal grains of arbitrary crystal symmetry. In term of this work, one can predict both the scattering-induced attenuation and phase velocity from Rayleigh region (wavelength >> scatter size) to geometric region (wavelength << scatter size) for an arbitrary incident wave mode (quasi-longitudinal, quasi-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 78 publications
(324 reference statements)
0
7
0
Order By: Relevance
“…Our method is inspired by, and builds on, the methodology of Gusmeroli et al [21] and Lutz et al [37], but is free of constraints that the ODF must be of a predetermined type, made possible by expanding the c-axis distribution function in terms of a spherical harmonic series (non-parametric approach) similar to developments made in the broader material sciences community (e.g. [44,50,5355]). Using the same ice-core data as Lutz et al [37] from the shear margin of Priestley glacier, Antarctica, we demonstrated that our method is a feasible approach for inferring both the ODF of ice-core samples and the effective grain elastic parameters of the homogenization scheme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our method is inspired by, and builds on, the methodology of Gusmeroli et al [21] and Lutz et al [37], but is free of constraints that the ODF must be of a predetermined type, made possible by expanding the c-axis distribution function in terms of a spherical harmonic series (non-parametric approach) similar to developments made in the broader material sciences community (e.g. [44,50,5355]). Using the same ice-core data as Lutz et al [37] from the shear margin of Priestley glacier, Antarctica, we demonstrated that our method is a feasible approach for inferring both the ODF of ice-core samples and the effective grain elastic parameters of the homogenization scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we extend the methodology of Gusmeroli et al [21] and Lutz et al [37] by reformulating the optimization (inverse) problem such that no particular fabric anisotropy is presupposed, made possible by expanding the c-axis ODF in terms of a spherical harmonic series, inspired by the broader material sciences community (e.g. [44,50,5355]). Using this representation, we demonstrate how either the ODF can be inferred if the effective elastic parameters of grains are known or vice-versa, followed by discussing the well-posedness of the inverse problem, relevant for future applications in glaciology, geology and elsewhere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used waveforms for ultrasonic nondestructive testing are shear wave and longitudinal wave [19]. The propagation speed of transverse waves Wireless Communications and Mobile Computing and longitudinal waves are different, and the particle will cause the superposition of the two vibrations, and then, the conversion of vibration modes will occur.…”
Section: Acoustic Detection Methodmentioning
confidence: 99%
“…Rokhlin et al [37] presented a model that includes second-order multiple scattering, applicable to all frequency ranges, providing small relative errors on both longitudinal and transverse attenuations for low anisotropy. Sha [38] extended the second-order attenuation (SOA) model for elastic waves in texture-free materials to textured polycrystals with ellipsoidal grains of arbitrary crystal symmetry. The predicted attenuation results of this work agree well with the literature on a textured stainless steel polycrystal.…”
Section: Introductionmentioning
confidence: 99%